Bibliometric analysis and visualization of online education in sports - Tong Zhou (Cogent Social Sciences)
The study focuses on how online education is used in the sphere of sports from 2001 to 2022. Especially in the era of COVID-19 popularity, the deepening cross-fertilization between the field of sports and other fields, coupled with the fact that scholars have not yet analyzed and organized the areas in which online education is combined with sports, and what opportunities there will be for the development of online education in the field of sports. In this article, it summarizes the past two decades of research with bibliometric and scientometric research methods, quantitatively exploring the development paths, research hotspots, and evolutionary trends in the field under the online medium, and systematically integrates the field through knowledge mapping to suggest and indicate the development process for the combination of the sports field and online education. The information of authors, keywords, and the number of national publications are used to determine that online education will continue to be studied in the field of sports with high explosive keywords such as children, online education, and COVID-19. This will provide suggestions and directions for the development of the sports field and online education.